A comprehensive model for phase noise characteristics of an optoelectronic oscillator. Issue 9 (11th August 2018) - Guo, Jiao Jiao; Jin, Xiang Dong; Zhu, Yan Hong; Jin, Xiao Feng; Chi, Hao; Zheng, Shilie; Zhang, Xian Min
Abstract: A comprehensive model for phase noise characteristics of an optoelectronic oscillator (OEO) is presented. The phase noise distributions of an OEO especially near the carrier are explained comprehensively, combining the Yao‐Maleki model and Leeson model. An experiment is carried on for verification of the OEO's phase noise distribution. Based on the comprehensive model, the phase noise distribution of an OEO can be predictably designed.